3h+4=4h-(h-3)

Simple and best practice solution for 3h+4=4h-(h-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3h+4=4h-(h-3) equation:


Simplifying
3h + 4 = 4h + -1(h + -3)

Reorder the terms:
4 + 3h = 4h + -1(h + -3)

Reorder the terms:
4 + 3h = 4h + -1(-3 + h)
4 + 3h = 4h + (-3 * -1 + h * -1)
4 + 3h = 4h + (3 + -1h)

Reorder the terms:
4 + 3h = 3 + 4h + -1h

Combine like terms: 4h + -1h = 3h
4 + 3h = 3 + 3h

Add '-3h' to each side of the equation.
4 + 3h + -3h = 3 + 3h + -3h

Combine like terms: 3h + -3h = 0
4 + 0 = 3 + 3h + -3h
4 = 3 + 3h + -3h

Combine like terms: 3h + -3h = 0
4 = 3 + 0
4 = 3

Solving
4 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4-7+-24-112+6= | | 3y+9=3y-3 | | 36v^2=4v | | 2(6-5e)= | | 12x+4y+17x-y=90 | | g(x)=x^3-8x+6 | | 2x^5= | | -5(-2a+3)-8=0 | | 2m+4m=24msolve | | H+1=-3 | | 130+140+115+x+90+130+x+65+x+80=900 | | 5+5n=4n-2 | | 6c-7c=5 | | r+522=-290 | | 7-4a=2(a+2) | | g=12+9g | | 500-232=4x | | x+771=1659 | | 12x+4y=90 | | 28=7/4x | | a-804=-1792 | | Y-4=9/5(x-5) | | 36=n-135 | | 0.03+0.03+0.02x=32 | | 9/15=9/25 | | a-267=-1251 | | -3k-3k-11=k+3 | | F(x)=7x^4-3x+x^2+5x-9x | | x-.20+x+.10=4.40 | | (6x+5)-(2x-5)= | | 9-10x=-11 | | v+77=141 |

Equations solver categories